Estudantes com doença crônica e/ou deficiência com comorbidade: ações escolares em prol da inclusão escolar - Marchi, Gabriela Guimarães (Universidade Federal de São Carlos, 2022)
Education is a right for all, and education must be based on equity, offering opportunities and conditions for children and adolescents to access and remain in school. Inclusive policies aimed at access to education emerged in the 1990s and were important movements for inclusion and access to services that help students meet their educational demands and needs, important rights for students with chronic diseases and also with disabilities with comorbidities. The objective of the research was to investigate the prevalence of chronic diseases and/or disabilities with comorbidities in students from municipalities belonging to a Regional Health Department in the interior of the state of São Paulo, as well as to identify the actions carried out in the school context to minimize the difficulties in the schooling process of these students. The research has a descriptive-exploratory nature and a qualitative-quantitative approach, which was carried out virtually. The first contacts were made through e-mails and telephone calls, and the participants were professionals in the area of ​​Education related to the Municipal Secretariats/Departments of Education or Municipal Educational Institutions who answered an online questionnaire. Of the 23 municipalities selected for the survey, nine municipalities responded, resulting in a total of twelve responses (one Department of Education, one Secretariat of Education, and 10 municipal schools). With the responses obtained from the questionnaire, it was possible to verify a higher prevalence of enrollments of students with chronic diseases in relation to students with disabilities with comorbidities. Bronchial asthma, the chronic disease, and Down syndrome and heart disease, the disabilities with comorbidities, had the highest prevalence among the number of students outlined by the municipalities in the years 2017 to 2020. Public policies are important to ensure the right and services to quality education for all, and to try to ensure that there are no absences and consequences for students, including those undergoing health treatment, whether due to chronic disease or disability with comorbidities, among others.
Students with chronic illness and/or disability with comorbidity: school actions in favor of school inclusion
Keywords: Educação especial; Doença crônica; Deficiência com comorbidade; Inclusão escolar; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL